The Use of Matching Game to Improve Young Learners Vocabulary Mastery in Descriptive Text: A Case of Students’ Eighth Grade SMP Negeri 1 Semarang - Rizky, Witania Amanda; Wiyaka, Wiyaka; Lestari, Yosephin Widarti (Jurnal Riset Ilmu Pendidikan, 2025)
This research aimed to investigate the effectiveness of using vocabulary matching games in improving young learners’ vocabulary mastery. Conducted at SMP Negeri 1 Semarang, the study employed a quasi-experimental design involving two eighth-grade classes: one as the experimental group using vocabulary matching games, and the other as the control group using traditional methods. Pre-tests and post-tests were administered to both groups to assess vocabulary development. The findings revealed a significant improvement in the experimental group’s vocabulary mastery, with the average score increasing from 62.85 to 78.62, while the control group improved from 52.65 to 65.41. An independent samples t-test showed a p-value of 0.020, indicating a statistically significant difference between the two groups. The results support the idea that game-based learning fosters active engagement, better retention, and enhanced motivation among students. This research further aligns with previous studies that emphasize the pedagogical benefits of interactive vocabulary instruction. In conclusion, vocabulary matching games proved to be an effective instructional strategy for enhancing vocabulary acquisition and should be considered as a valuable tool in language learning classrooms.